Cryopreservation of Human Oligoasthenoteratozoospermic Spermatozoa With Polyvinylpyrrolidone - Hapon, Hanna; Pavlovich, Olena (Problems of Cryobiology and Cryomedicine, 2020)
Probl Cryobiol Cryomed 2020; 30(3): 296